PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS V SD UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Winda Sari Br Panjaitan; Safrida Napitupuluh; Nila Lestari; Abdul Mujib; Dalimawaty Kadir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Student Worksheets (LKPD) based on Problem Based Learning (PBL) in mathematics learning of fractions in grade V of Elementary School to improve student learning outcomes. This study uses the ADDIE development model consisting of five stages, but limited to the Development stage. The subjects of the study were grade V students of SD Negeri 006 Melayu Besar. Data collection was carried out through expert validation, teacher and student response questionnaires, and learning outcome tests. The validation results showed that the LKPD developed was in the "very feasible" category, with a score from design experts of 95% and from material experts of 87.5%. The trial was carried out in two stages, namely a small group trial of 5 students who obtained a practicality result of 92.6%, and a large group trial of 20 students with a practicality result of 93.5%. To measure the effectiveness of LKPD on improving student learning outcomes, an initial test (pretest) and a final test (posttest) were used. Based on data analysis, the average N-Gain was 0.71 which is included in the "high" category. Thus, the LKPD based on Problem Based Learning that was developed is declared valid, practical, and effective for use in learning mathematics on fraction material to improve the learning outcomes of fifth grade elementary school students.